PENGARUH TEKNIK MASSAGE BACK-EFFLEURAGE TERHADAP PENGURANGAN RASA NYERI PERSALINAN KALA I DI KLINIK BERSALIN KURNIA KECAMATAN DELITUA KABUPATEN DELI SERDANG - Suriani Suriani; Ela Nuraini; Nurul Aini Siagian (Jurnal Penelitian Keperawatan Medik, 2019)
This study aims to determine the effect of Back-Effleurage Massage Technique on Reduction of First-Stage Labor Pain in Kurnia Maternity Clinic, Delitua District, Deli Serdang Regency. This study uses a Quantitative Analytical Method with a Quasy-Experimental research design with the One Group Pretest-Posttest approach. Data collection techniques using observation sheets. This Back-Effleurage Massage Technique is carried out for 20 minutes/hour during a contraction. The population in this study were 25 pregnant women entering Trimester III. The sampling technique used is the Total Sampling Method. Data analysis using Paired Sample T Test. The results of this study were obtained that the administration of Back-Effleurage Massage Technique on the abdomen at the Kurnia Maternity Clinic can reduce labor pain from mothers who experience moderate pain to mild pain and mothers who experience severe pain to moderate pain. It can be concluded that there is a significant effect with the giving of the Back-Effleurage Massage Technique on the reduction of Stage I labor pain.